Agency and role models: do they matter for adolescent girls' sexual and reproductive health? - Bolatito O. Ogunbiyi; Sarah Baird; Jeffrey B. Bingenheimer; Amita Vyas (BMC, 2023)
Abstract Despite recent declines in early childbearing in Ethiopia, improved sexual and reproductive health continues to elude many adolescent girls, partially due to constrained agency and role models. This study examined the relationship between agency, role models and two sexual and reproductive health outcomes, ideal age at childbirth and attitude towards gender-differentiated parental control, among adolescent girls in Ethiopia. Agency and role model presence were positively associated with ideal age at childbirth (β = 0.23, p < .01 and β = 0.77, p < .001, respectively). Having family members, friends or famous individuals as role models was significantly associated with an increase of 1.45 years (p < .01), 1.32 years (p < .05) and 1.01 years (p < .01) in ideal age at childbirth, respectively, compared to having no role model. Agency was positively associated with attitude towards gender-differentiated parental control of adolescent behaviors (OR = 1.18, p < .001). This study highlights the need for interventions aimed at increasing agency and providing role models for adolescent girls.